2020
DOI: 10.1080/13880209.2020.1821066
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Naoxintong capsule alone and in combination with ticagrelor and atorvastatin in rats with Qi deficiency and blood stasis syndrome

Abstract: Context: Naoxintong Capsule (NXT), a Chinese medicine, has been widely used for the treatment of coronary heart disease (CHD) in clinics. Objective: This study evaluated the cardioprotective effects of NXT alone and in combination with ticagrelor (TIC) and atorvastatin (ATO). Materials and methods: Qi deficiency and blood stasis rats were established by 8 weeks high fat diet feeding and 16 days exhaustive swimming and randomly divided into seven groups, that is, NXT (250, 500 and 1000 mg/kg/d), TIC (20 mg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Yang et al suggested that the combination of NXT and atorvastatin could, on one hand, enhance plaque stability and, on the other hand, attenuate atorvastatin-induced acute liver inflammation ( Yang et al, 2017 ). In addition, we have demonstrated that NXT administration could attenuate atorvastatin induced excessive oxidative stress, hepatic and renal dysfunction, inflammatory activation, and endothelial integrity ( Zhang et al, 2020a ). These drug combination studies suggest that the co-treatment of NXT to atorvastatin can enhance safety and efficacy.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Yang et al suggested that the combination of NXT and atorvastatin could, on one hand, enhance plaque stability and, on the other hand, attenuate atorvastatin-induced acute liver inflammation ( Yang et al, 2017 ). In addition, we have demonstrated that NXT administration could attenuate atorvastatin induced excessive oxidative stress, hepatic and renal dysfunction, inflammatory activation, and endothelial integrity ( Zhang et al, 2020a ). These drug combination studies suggest that the co-treatment of NXT to atorvastatin can enhance safety and efficacy.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…PAF also stimulates the biosynthesis of other inflammatory mediators (especially PG and LT). Research has suggested that Chinese medicines such as Ginkgo diterpene lactones, 55 Naoxintong Capsule 56 and others can inhibit these vasoactive mediators.…”
Section: The Classic Mechanisms Of the Anti‐inflammatory Effects Of T...mentioning
confidence: 99%
“…Zhang et al. found that the combination of NXT and lipid‐lowering drugs effectively alleviated the blood stasis (Zhang et al., 2020). Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…This drug has the effect of replenishing qi, improving blood circulation and removing blood stasis, and it is primarily used to treat coronary heart disease, ischemic cerebrovascular disease, angina pectoris, and stroke (GBD 2016 Disease andInjury Incidence andPrevalence Collaborators, 2017;Yellon & Hausenloy, 2007). Zhang et al found that the combination of NXT and lipid-lowering drugs effectively alleviated the blood stasis (Zhang et al, 2020). Wang et al found that NXT could prevent the vascular injury form of ischemia by regulating the COX2/NF-κB pathway (Wang et al, 2021).…”
mentioning
confidence: 99%